2017
DOI: 10.1115/1.4035647
|View full text |Cite
|
Sign up to set email alerts
|

The Interface of Mechanics and Nociception in Joint Pathophysiology: Insights From the Facet and Temporomandibular Joints

Abstract: Chronic joint pain is a widespread problem that frequently occurs with aging and trauma. Pain occurs most often in synovial joints, the body's load bearing joints. The mechanical and molecular mechanisms contributing to synovial joint pain are reviewed using two examples, the cervical spinal facet joints and the temporomandibular joint (TMJ). Although much work has focused on the macroscale mechanics of joints in health and disease, the combined influence of tissue mechanics, molecular processes, and nocicepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 173 publications
(294 reference statements)
0
24
0
1
Order By: Relevance
“…This study used the RGS to assess spontaneous pain in a rat model of TMJ pain and compared RGS between groups with different TMJ sensitivity profiles to evaluate its ability to differentiate pain states (Figs 3 and 4 ). Although facial grimace scales have been used to characterize visceral, inflammatory, and neuropathic pain in rodent models of skin and joint inflammation, cervical radiculopathy, peripheral neuropathy, bladder infection, and abdominal constriction 16 , 18 , 19 , 41 , this is the first report of facial grimace for TMJ pain and in the context of repeated joint over-loading, which is a major cause of joint degeneration and pain 42 45 . Since RGS is elevated over baseline during the TMJ loading period and one day after its cessation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the RGS to assess spontaneous pain in a rat model of TMJ pain and compared RGS between groups with different TMJ sensitivity profiles to evaluate its ability to differentiate pain states (Figs 3 and 4 ). Although facial grimace scales have been used to characterize visceral, inflammatory, and neuropathic pain in rodent models of skin and joint inflammation, cervical radiculopathy, peripheral neuropathy, bladder infection, and abdominal constriction 16 , 18 , 19 , 41 , this is the first report of facial grimace for TMJ pain and in the context of repeated joint over-loading, which is a major cause of joint degeneration and pain 42 45 . Since RGS is elevated over baseline during the TMJ loading period and one day after its cessation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Since these key features are shared across different synovial joints with OA (Tonge et al 2014;Sperry, Ita, et al 2017), the broader literature provides mechanistic insights into joint degeneration and disability. OA is initiated by multiple factors, including injury, aging, abnormal joint mechanics, and atypical joint shape (Loeser et al 2012).…”
Section: Osteoarthritis Painmentioning
confidence: 99%
“…3 A number of systemic risk factors for OA have been described, including age, gender, ethnicity, hormones, genetics, obesity, and nutrition, as well as biomechanical factors, including prior injury, muscle weakness, joint deformity, and ligament laxity. 1,[4][5][6] Despite the growing awareness of these risk factors, the pathophysiology of OA is still unresolved. Emerging clinical and experimental research suggests that the nervous system may play an essential role in mediating the pathophysiology and symmetrical manifestation of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging clinical and experimental research suggests that the nervous system may play an essential role in mediating the pathophysiology and symmetrical manifestation of OA. 4,5,7,8 OA has been traditionally considered an asymmetrical disease; however, studies have shown a predilection over time in humans toward symmetrical involvement, especially in knees 9 and hands. 10 Research shows that experimentally induced unilateral knee OA in animals results in symmetrical spread of neurogenically mediated inflammation and articular degeneration to contralateral homologous joints.…”
Section: Introductionmentioning
confidence: 99%